ChatGPT in Organic Chemistry Classrooms: Analyzing the Impacts of Social Environment on Students’ Interest, Critical Thinking and Academic Achievement - Babalola, Victor Tubosun; Suwaiba Said Ahmad; Halima Sani Tafida (Yayasan Nurul Yakin Bunga Tanjung, 2024)
This study aims to analyze the Impacts of Social Environment on Interest, Critical Thinking and Academic Achievement of Students Taught Organic Chemistry Using Artificial Intelligence ChatGPT. Correlational research design was engaged for the study. 50-students in SS3 with an average age of 17years, who have access to android phones and the ChatGPT application from two senior secondary schools in Gwale Local Government area of Kano State, Nigeria formed the study sample. The instruments used for data collection include; the students’ social environment, interest and critical thinking questionnaire (r=0.96) and Organic Chemistry Achievement Test (r=0.92). The data were analyzed using mean, standard deviation and Spearman Rank Order Correlation. The study revealed a high positive correlation between the social environment and student’s interest; Social environment and critical thinking; as well as social environment and students’ achievement in the ChatGPT’s Organic Chemistry Classroom. The study further found a strong positive correlation between the students’ interest and critical thinking, critical thinking and students’ achievement in Organic Chemistry among students in the ChatGPT condition. It was concluded that social environment has a strong positive impact on students’ interest, critical thinking and academic achievement in organic chemistry among students in the ChatGPT classrooms. The study recommends that, as the artificial intelligence (AI) ChatGPT is migrating into the chemistry classrooms, government needs to re-train chemistry teachers, school librarians and lab-technologists through refreshers courses to improve their performance in the concepts